The correlation between vitamin D and levels of IFN-γ, NF-κB, thyroid antibodies in down syndrome: study in Indonesian children - Yuni Hisbiyah, -
Abstract Background and aim: Vitamin D (VD) reduces interferon-gamma (IFN-γ) production and prevents nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) activation, impacting the inhibition of the autoimmunity process such as autoimmune thyroiditis (AITD). Children with Down syndrome (DS) are reported to have a higher risk of autoimmunity and lower VD levels than non-DS. Therefore, this study aimed to evaluate VD levels in Indonesian DS children and their relationship with marker of AITD.